1997
DOI: 10.1021/ac961099o
|View full text |Cite
|
Sign up to set email alerts
|

Cation Selectivity of Natural and Synthetic Ionophores Probed with Laser-Induced Liquid Beam Mass Spectrometry

Abstract: The novel laser desorption method laser-induced liquid beam ionization/desorption (LILBID) is applied to the mass spectrometric examination of selective ion binding by natural and synthetic ionophores in methanol solutions. The ions are desorbed from a liquid jet with an IR laser pulse and then extracted perpendicularly into a reflectron time-of-flight (RE-TOF) analyzer. LILBID studies on the natural ion carriers valinomycin and monensin A are presented, as well as those on the synthetic crown ethers 18-crown-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…1). In addition, the polar functionality of these compounds can orient toward the cation with the outer solvent accessible portion of the molecule being largely hydrophobic [44][45][46][47], resulting in some degree of metal encapsulation [6,46,48]. In addition, the polar functionality of these compounds can orient toward the cation with the outer solvent accessible portion of the molecule being largely hydrophobic [44][45][46][47], resulting in some degree of metal encapsulation [6,46,48].…”
Section: Sorption Experimentsmentioning
confidence: 99%
“…1). In addition, the polar functionality of these compounds can orient toward the cation with the outer solvent accessible portion of the molecule being largely hydrophobic [44][45][46][47], resulting in some degree of metal encapsulation [6,46,48]. In addition, the polar functionality of these compounds can orient toward the cation with the outer solvent accessible portion of the molecule being largely hydrophobic [44][45][46][47], resulting in some degree of metal encapsulation [6,46,48].…”
Section: Sorption Experimentsmentioning
confidence: 99%
“…CEs can include not only ionic species but also various neutral ones through noncovalent interactions, such as van der Waals force and hydrogen bonding. The metal ion-CE complexes were extensively investigated in the gas phase with mass spectrometric techniques [15][16][17][18][19][20][21][22][23][24][25][26][27] and ion mobility methods. [3][4][5][6][7][8][9][10][11][12][13][14] One of the important aspects of CEs in the host-guest system is their selectivity of guest species.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] For example, 18-crown-6 (18C6) forms an exceptionally stable 1:1 complex with K + compared to other alkali metal cations in aqueous solution, [1,3] which is described by the best matching between the size of crown cavity and that of the spherical K + ion. The metal ion-CE complexes were extensively investigated in the gas phase with mass spectrometric techniques [15][16][17][18][19][20][21][22][23][24][25][26][27] and ion mobility methods. [28,29] It was found that the property of CEs in the gas phase is different from that in solution; 18C6 does not show a largest binding energy with K + among the alkali metal cations.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] In the condensed phase, the complex structures are studied by UV, IR, NMR, and X-ray diffraction methods at room temperature in bulk conditions. In the gas phase, metal ion (M 1 )•CE complexes have been extensively investigated with mass spectrometric techniques, [15][16][17][18][19][20][21][22][23][24][25] ion mobility methods [26,27] in the 1990s, and more recently, by IR spectroscopy. [28][29][30][31][32][33][34] CEs have flexible frames and the thermal energy at room temperature is equal to the host-guest interaction energy, so the observed spectra are often complicated, due to the average of all possible conformers and fluctuation between them at a given temperature.…”
Section: Introductionmentioning
confidence: 99%